CO2 photoreduction to hydrocarbons and oxygenated hydrocarbons - Sim, Lan Ching; Yee, Pey Li; Leong, Kah Hon; Azrina, Abd Aziz; Hossen, Md. Arif (Elsevier, 2024)
Photoreduction of CO2 to hydrocarbons and oxygenated hydrocarbons can be realized through various ways, such as photocatalytic, photothermal catalytic, solar-driven reverse water–gas shift, and photoconversion of algal system. Among these methods, photocatalytic presents a sustainable way for photoreduction of CO2 because this process can be achieved in the presence of H2O and sunlight which are readily available. This chapter highlights the main challenges of photocatalytic process, such as the high energy barrier of CO2 molecules, electron loss, and wide band gap of photocatalyst and unfavorable side reactions. Although industrial-scale application of photoreduction of CO2 in the current market is scant, there are numerous advances done in the engineering aspect of the process to improve photocatalytic performance. The recent efforts mainly focused on the modification of photocatalysts especially titanium dioxide (TiO2) through metal/nonmetal doping, facet engineering, and the design of photoreactor. In this chapter, we mainly focus on the principles and procedures, process, and recent applications of the CO2 photoreduction to hydrocarbons and oxygenated hydrocarbons. The challenges and future perspectives in this field are listed as well.